Phonological, Morphological and Syntactical Influences of Mother Tongue on Arab Learners - Taj Mohammad (University of Kuningan, 2015)
Arab learners' mother tongue influence on target language (English) is a very usual and well-known phenomenon in schools and universities. The present study attempts to find and analyze phonological, morphological and syntactical influences of mother tongue on Arab learners. The study aims to critically analyze students’ writing samples and focus on the problems like capitalization, punctuation, language use and spelling. It critically diagnoses teachers’ perception on the above-mentioned writing problems through a personal interview and offers some recommendations based on the findings through writing samples and interview responses. To achieve these objectives, researcher analyzes forty writing samples of students from first and second midterm examinations at PYP (Preparatory Year Program), Najran University. To the surprise of researcher, writing samples had ridiculous errors. Four writing samples are attached to expose errors of students. Twenty teachers, especially teaching writing at PYP, Najran University, were interviewed in order to investigate the real causes of extremely poor performance of students. Teachers, in the interview, denoted various causes for the present condition of students. They admitted that use of mother in the classroom was one of the major causes of the present condition of students. The study offered some recommendations (based on the findings) like elimination of GT method and implementation of CLT approach in the classroom.Key words: GT method, mother tongue influences, target language